Analisis Kinerja Keuangan Sebelum dan Saat Pandemi Covid-19 terhadap Risiko Kebangkrutan Perusahaan: Studi pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021 - Rinofah, Risal; Maulida, Alfiatul; Sari, Risa Puspita (Jurnal Maksipreneur, 2024)
This study aims to determine differences in the company's financial performance before and during the Covid-19 pandemic, as well as to determine the effect of financial performance before and during the Covid-19 pandemic on the risk of company bankruptcy. The sample used in this study is a state-owned company listed on the Indonesia Stock Exchange (IDX) for 2018-2021. Sampling using purposive sampling method and obtained 21 companies. The tests used to determine the differences in this study were the paired samples t-test and the Wilcoxon signed ranks test, while the performance effect test on the risk of bankruptcy was measured using the modified Altman Z-score formula and multinomial logistic regression analysis. The results showed that the results of the different tests using the Paired samples t-test, i.e. the Debt to Asset Ratio (DAR) ratio before and during the Covid-19 pandemic, there was no significant difference, but when tested differently using the Wilcoxon Signed Rank Test, i.e. the ratio of return on assets (ROA), return on equity (ROE), debt to equity ratio (DER) there are significant differences both before and during the Covid-19 pandemic, while for the current ratio (CR) and quick ratio (QR), there is no significant difference. While the results of the influence test using a multinomial logistic regression test, the Current Ratio (CR_SBL) before the Covid-19 pandemic and Return on Assets (ROA_ST) during the Covid-19 pandemic had a significant effect on the risk of bankruptcy of BUMN companies, but for other ratios, it had no significant effect. Against the risk of bankruptcy before and during the Covid-19 pandemic.